Pembinaan Terhadap Anak Binaan Residivis Di Lembaga Pembinaan - Gabriella Fenisia Klarci Elias; John Dirk Pasalbessy; Hadibah Zachra Wadjo (Faculty of Law Pattimura University, 2023)
Introduction: The child is the mandate of God Almighty, who has the dignity and dignity of the whole person.Purposes of the Research: Analyze and describe the forms of fostering recidivist foster children at the Class II Ambon Special Children Development Institution and the influence between the results of fostering fostered children and criminal acts that were committed later. Methods of the Research: This research uses a research approach carried out juridically empirically. The data sources collected used field research (interviews) and literature research, using primary and secondary data. Data analysis using qualitative data analysis.Results of the Research: Based on the results of research and discussion, it can be concluded that the form of coaching for Recidivist Fostered Children at the Ambon Class II Children's Special Development Institution at the time of coaching includes: Personality Coaching, Skills Development, and Formal and Non-Formal Education and the influence between the results of coaching fostered children and criminal acts committed then there is no influence on the results of coaching fostered children, because when the child returns to society the child has no confidence and no energy to act positively. Thus it will have a negative effect and there are opportunities that make children look at their world unkindly, feel that they are not treated fairly and create the potential for frustration to commit crimes in the future which results in no deterrent effect so as to cause a repeat of crimes in the future.